La Evasión del impuesto a la venta del arroz pilado en la comercialización por las empresas molineras y su incidencia en el desarrollo socio-económico en la provincia de San Martin. Periodo 2013 - Hidalgo Pinedo, Sharon (2015)
This thesis has as main objective to determine the factors causing tax evasion Sale of milled rice. Given that tax evasion is a serious state for waiver providing the necessary revenue to finance public spending. The more evasion exists, the less chance the state to cover their essential expenses. Also evasion has perverse effects on the market economy , as is a form of unfair competition , because the act of economic agents will not guided by their efficiency , but by the varying performance of the obligations tax. The preservation of democratic governance in countries like Peru, is urgently address the serious structural problems relating to social issues such as access to education, health, and poverty alleviation. However, there is an undeniable reality, which is the limitation of tax revenues. Faced with this harsh landscape, it is up to the Peruvian Tax Administration develop an action priority: strive to raise ever greater extent tribute generating marketing milled rice. That is, directly combat tax evasion in order to reduce it to a point where the gap between the amount of potential collection and effective collection resulting insignificant. Moreover, the informal economy is the existence of economic activities taking place without the knowledge and, therefore, the control of tax authorities. The high degree of informality, reflected in the high levels of tax evasion, they represent a major loss of resources for the treasury. Actions and strategies that the Peruvian Tax Administration has implemented since 2002, with the establishment of the withholding system, perceptions and detractions, intended to close these gaps failure to tax the sale of milled rice (MVI). The strategy to combat tax evasion requires a social and political legitimacy. Indeed, in a democratic society, taxes are set by laws emanating from the will of the people, expressed through their legitimate representatives. Therefore, the fight against tax evasion can not be understood otherwise than that of giving effect to the expressed will of the people as well. The process of legitimation and "awareness" of the fight against tax evasion must start from the fact that citizens are convinced that this is a problem for all and that tax evasion involves a reduction in the financial resources of the state, reducing their actions to adequately provide public goods and services. Getting to know with any degree of certainty the level of tax evasion in a country is useful for all Tax Administration. Thus we can approach this issue in various ways, so that it can complement and corroborate the results obtained with standard methodologies known. Actions and strategies the A simple way is to ask the taxpayers themselves what they think is the extent of tax evasion. This measure has been implemented due to high informality and tax evasion that exists in the marketing of milled rice. The most common way of evading the tax is the use of vouchers and reference guides and fake suppliers of nonexistent people. This tax evasion, informal constant mills, left at a disadvantage to existing and formal mills, and also requires evade.Through this study showed lack in oversight of the Tax Administration in Marketing milled rice ; which generates tax evasion Sale Milled Rice ( MVI ) .